Executive Function in Young Children: Validation of the Preschool Executive Task Assessment - Yael Fogel; Ortal Cohen Elimelech; Naomi Josman (Children)
Background: Executive function—the cognitive processes and abilities used to perform daily activities and solve real-world problems—is crucial for children’s development. However, existing assessments often lack ecological validity, limiting their ability to reflect real-world cognitive performance. This study aims to validate the Preschool Executive Task Assessment (PETA) as a performance-based ecological measure of executive functions in typically developing Israeli children. Methods: Thirty-six typically developing children participated. Parents completed a demographic questionnaire and the Child Evaluation Checklist, while children undertook two Wechsler Intelligence Scale for Children–Revised 95 subtests. Eligible participants completed three performance-based assessments: PETA, the Children’s Kitchen Task Assessment (CKTA), and the Do-Eat. Inter-rater reliability was examined using the intraclass correlation coefficient (ICC), and concurrent validity was assessed via correlations with the CKTA and Do-Eat scores. The Benjamini–Hochberg correction method was used to control false-positive findings. Results: Age showed weak-to-moderate correlations with key performance measures, including total score, completion time, and required cues (−0.48 < r < −0.37, p < 0.05), indicating improved PETA performance with age. Inter-rater reliability for the PETA was high (ICC = 0.84). Significant correlations were found between the PETA completion time and CKTA total score (r = 0.42, p = 0.014), and between working memory and the CKTA total score (r = −0.44, p = 0.008). Additionally, significant correlations were found between the PETA and the Do-Eat (−0.69 < r < 0.55). Conclusions: Although further research is needed to refine its use across diverse populations and settings with larger samples, these preliminary findings support the PETA’s reliability and validity as a performance-based executive function assessment in young children. This study advances ecologically valid assessments and aids clinicians in selecting appropriate tools for evaluating executive functions in early childhood.